Health Protocol Compliance by Staff and Guests as Sustainable Behavior in Star Hotels of South Sulawesi - Muhtasom, Ali; Arief, Arnie; Royanow, Achlan Fahlevi (Politeknik Pariwisata Makassar, Indonesia, 2025)
This study aims to evaluate the compliance of star-rated hotels in South Sulawesi with health protocols as a form of sustainable behavior that contributes to sustainable tourism. Using a quantitative survey method, the research focuses on four dimensions: Cleanliness, Health, Safety, and Environmental Sustainability. Data was collected from hotel management, staff, and guests to capture a comprehensive perspective on protocol implementation. The findings indicate a high level of compliance overall, reflecting strong support for sustainable tourism practices. However, areas related to cleanliness and environmental sustainability need improvement. Therefore, hotels should continuously strengthen these aspects to ensure health-related practices are fully integrated into long-term tourism development.